The Impact of Chronic Heart Failure Treatment on Glycemic Variability in Patients without Diabetes Mellitus - Georgiy B. Mankovsky; Yevhen Yu. Marushko; Yanina A. Saienko; Ivanna V. Zubovych; Yana Yu. Dzhun; Olha O. Monashnenko; Nadiya M. Rudenko; Borys M. Mankovsky (Ukrainian Journal of Cardiovascular Surgery, 2023)
Background. According to statistics, about 26 million people worldwide suffer from heart failure (HF). Currently, sodium-glucose cotransporter 2 inhibitors are widely prescribed for treatment of HF with reduced left ventricular ejec-tion fraction (LVEF) throughout the world. Therefore, prescribing drugs that have anti-hypoglycemic effect in patients without diabetes mellitus still raises some concerns, considering the possible risk of developing hypoglycemia.The aim. To assess the effect of dapagliflozin on glycemic variability in treatment of HF with reduced LVEF in patients without diabetes mellitus.Materials and methods. The study was conducted at the premises of the Department of Cardiometabolic Diseases of the Ukrainian Children’s Cardiac Center. Twenty-three patients with HF with reduced LVEF of various etiologies without diabetes mellitus were evaluated. The variability of glycemia in the study group was assessed using continuous glucose monitoring. For this, the MiniMed iPro2 continuous glucose monitoring system (Medtronic, USA) was used.The sensor was inserted on day 1 and removed on day 7. Average value of glycemia during the day, time in range (TIR) and time below range (TBR) were calculated on the basis of data about the level of glucose in the intercellular fluid obtained for 6 days of monitoring. Dapagliflozin 10 mg once a day was prescribed to all the patients included in the study for the treatment of HF with reduced LVEF. The average follow-up period was 7 months.Results. The examined patients were divided according to clinical and laboratory characteristics. Assessment of daily variability of glycemia during 6 days of observation using continuous glucose monitoring in patients on dapagliflozin revealed average blood glucose level from 4.4 mmol/L (minimum value) to 6.0 mmol/L (maximum value). These results indicate minimal risk of hypoglycemia and safety of using dapagliflozin in case of HF with reduced LVEF without concomi-tant type 2 diabetes mellitus. TIR and TBR indicators were also evaluated in patients with and without prediabetes. The obtained data allows to assert the same safety of taking dapagliflozin in both these groups, due to the fact that time of glycemia <3.9 mmol/l does not exceed the indicator of 5%.Conclusion. The use of dapagliflozin as part of complex therapy of HF with reduced LVEF does not elevate the risk of developing hypoglycemia in patients without diabetes mellitus.